CSIG-21. BAF60C/SMARCD3 REGULATES TUMOR CELL DISSEMINATION IN MEDULLOBLASTOMA. (9th November 2020) - Hu, Baoli; Poore, Brad; Sharma, Vaibhav; Guan, Yongchang; Agnihotri, Sameer; Pollack, Ian; Hu, Baoli
Abstract: Medulloblastoma, the most common malignant brain tumor in children, is a diverse and heterogeneous disease. Molecular characterization of MB revealed four major subgroups, WNT, SHH, Group 3, and Group 4. Although surgical resection, radiotherapy, and chemotherapy are effective at eliminating some forms, patients with the aggressive tumors cannot be cured with conventional therapies, particularly in Group 3. Group 3 is the most aggressive subtype of this disease, accounting for about 25%-30% of cases, and characterized by frequent metastasis at diagnosis and the worst prognosis among all the subgroups. Metastatic dissemination is a major treatment challenge and strongly associated with poor prognosis in patients with medulloblastoma. However, the molecular mechanisms of tumor cell early dissemination and late metastasis remain largely unknown. Here, we found that Group 3 has elevated expression of BAF60C/SMARCD3, a subcomponent of SWI/SNF complex, which significantly mobilizes nucleosomes and remodels chromatin. Clinically, elevated SMARCD3 mRNA resulted in a poorer prognosis in medulloblastoma patients, which was further validated in 63 patient tumors by immunohistochemical staining for SMARCD3. Interestingly, tumors that had metastasized often had elevated expression of SMARCD3, in all subgroups of medulloblastomas and Group 3 only. An orthotopic mouse model further supported that SMARCD3 is highly expressed in metastatic tumors compared to primary tumors. Importantly, CRISPR-Cas9-mediated SMARCD3 deletion decreased cell migration and invasion in multiple medulloblastoma cell lines. Mechanistically, SMARCD3 deletion led to decreased H3K27me3, suggesting that SMARCD3 may cooperate with PRC2 in regulation of gene expression. Strikingly, SMARCD3 deletion downregulated Reelin signaling pathway, an essential role in neuronal positioning during neurodevelopment, which indicates that tumors with highly expressed SMARCD3 hijack a developmental signaling to promote their dissemination and aggressiveness. Together, our results suggest that inhibition of SMARCD3 controlling downstream signaling may effectively prevent tumor dissemination and improve clinical outcomes in children with medulloblastoma.